Strategic Polarization - Kalai, Adam Tauman; Kalai, Ehud (Journal of Mathematical Psychology, 2001)
In joint decision making, similarly minded people may take opposite positions. Consider the example of a marriage in which one spouse gives generously to charity while the other donates nothing. Such “polarization” may misrepresent what is, in actuality, a small discrepancy in preferences. It may be that the donating spouse would like to see 10% of their combined income go to charity each year, while the apparently frugal spouse would like to see 8% donated. A simple game-theoretic analysis suggests that the spouses will end up donating 10% and 0%, respectively. By generalizing this argument to a larger class of games, we provide strategic justification for polarization in many situations such as debates, shared living accommodations, and disciplining children. In some of these examples, an arbitrarily small disagreement in preferences leads to an arbitrarily large loss in utility for all participants. Such small disagreements may also destabilize what, from game-theoretic point of view, is a very stable equilibrium.